Desain dan Implementasi Standar Operasional Prosedur (SOP) Keamanan Sistem Informasi Fakultas Teknik Universitas Diponegoro Menggunakan Standar ISO 27001 - Penji Prasetya; Adian Fatchur Rochim; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
Like today's modern era, information technology is needed to support the business processes of the organization. In the use of information technology organization must have policies and standard operating procedures are good that any work carried out in the appropriate direction of the organization. Not only that, the organization must also pay attention to information security of any assets owned. This final project aims to make policies and standard operating procedures (SOP) and assessing the information security risk in the assets of the organization. In the process of this skripsi refers to the standard of ISO 27001 as the standard for information security management and use of qualitative methodology, where qualitative methodology is a methodology that produces descriptive data in the form of words written or spoken of people and behaviors that can be observed. This final project resulted in the level of risk that is contained in the value of assets and generate recommendations to improve the security controls in the information security of assets based on the clauses of ISO 27001. In accordance with the initial objective of this final project also produce information security policy document and document information security standard operating procedures.